Airlines and their Focus on Cost Control and Productivity - Martín, Juan Carlos; Román, Concepción (European Journal of Transport and Infrastructure Research, 2008)
Airline deregulation is an issue which has been attracting more attention, especially from the media, in recent years. In this paper, we analyze how the deregulation in the European Union has affected the behaviour of carriers, especially regarding the entrance of new Low Cost Carriers. Subsequently, we analyze how the former legacy carriers have reacted to this entrance studying issues such as the new focus on airline costs and productivity. We also present some evidence about the potential role which can be played by other sectors of the industry like airports, Air Traffic Management firms and aircraft manufacturers.